2021
DOI: 10.1590/1518-8345.4658.3465
|View full text |Cite
|
Sign up to set email alerts
|

Association and correlation between stress, musculoskeletal pain and resilience in nurses before hospital accreditation maintenance assessment

Abstract: Objective: to associate and correlate musculoskeletal pain, stress and resilience of nurses in the maintenance of Hospital Accreditation Certification. Method: longitudinal study in two moments, before and after the Accreditation maintenance visit, March and June 2019, with 53 nurses from a hospital institution. The data collected was: sociodemographic, clinical and occupational variables, stress, osteomuscular pain and resilience. Descriptive variables, Chi-square test, t test, Fisher’s exact test, Pearson’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…A systematic review that aimed to identify the main psychosocial factors in Nursing work indicated that the perception of justice, respect, support from supervisors and social inclusion favour the preservation of the mental health of Nursing workers 5 . The subjective and individual character in the perception of factors that contribute to stress and the need for health-promoting interventions focused on psychosocial characteristics, which enable the active participation of professionals, are highlighted 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review that aimed to identify the main psychosocial factors in Nursing work indicated that the perception of justice, respect, support from supervisors and social inclusion favour the preservation of the mental health of Nursing workers 5 . The subjective and individual character in the perception of factors that contribute to stress and the need for health-promoting interventions focused on psychosocial characteristics, which enable the active participation of professionals, are highlighted 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A study that evaluated the association between muscle pain, stress, and resilience of nurses during the Accreditation maintenance process, did not find any correlation between the variables studied, but identified a higher resilience capacity after the assessment, indicating that the stressors experienced during the process were faced in an adequate manner, constituting a positive factor for the maintenance of the professionals' health and quality of care. 25 Despite the already mentioned prevalence among hospitals in the list of accredited Brazilian establishments, it is noted that the Therapeutic Diagnostic-Support Units -which represented a computation of services that aid in the determination of diagnosis and/or complement the treatment and rehabilitation of the patient -and the clinics, polyclinics, and outpatient clinics accounted for about a quarter of the total number of certifications. Even if the survey did not make this distinction in the analysis (which can be interpreted as a limitation), it is hypothesized that these establishments concentrate a high proportion of the private sector, since it is possible that they are institutions with a clear market interest in health.…”
Section: Discussionmentioning
confidence: 99%
“…Una revisión sistemática que objetivó identificar los principales factores psicosociales en el trabajo de Enfermería, apuntó que la percepción de justicia, respeto, soporte de las jefaturas e inclusión social, favorecen la preservación de la salud mental del trabajador de la área (5) . Se destacan el carácter subjetivo e individual en la percepción de factores que contribuyen para el estrés y la necesidad de realizar intervenciones promotoras de la salud, enfocadas en características psicosociales que posibiliten la participación activa de los profesionales (28) .…”
Section: Discussionunclassified